2021
DOI: 10.1111/odi.13941
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as an adjunctive treatment on dental procedures: A systematic review

Abstract: The systematic review tried to answer the following question: Does the melatonin administered systemically or topically ameliorate patients involved with oral health conditions or dental procedures? The systematic review has been registered in the PROSPERO (2021CRD42021095959). Eligibility criteria included only randomized controlled clinical trials (RCTs) with at least 10 participants that compared patients that received melatonin as a treatment before and/or after their oral intervention topically or systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…A previous study review has shown that melatonin can reduce in ammation in dental clinical conditions [24]. Thus, melatonin may be considered as a potential reducer of the in ammatory process induced by endodontic sealers.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A previous study review has shown that melatonin can reduce in ammation in dental clinical conditions [24]. Thus, melatonin may be considered as a potential reducer of the in ammatory process induced by endodontic sealers.…”
Section: Discussionmentioning
confidence: 97%
“…Melatonin is a hormone produced especially in the pineal gland. Although its main action is to regulate the circadian rhythm [34], this molecule can modulate the in ammatory process, besides regulating the oxidative stress and the proliferation of tumoral cells [15,16,24]. These effects are due to its ability to penetrate cells, acting on their DNA and cell structures, such as the plasma membrane [37,38}.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations